Bacillus Cereus Contamination of UF‐Feta Cheese during Ripening and Shelf Life. Issue 1 (12th September 2014) - Moradi‐Khatoonabadi, Zhila; Ezzatpanah, Hamid; Maghsoudlou, Yahya; Khomeiri, Morteza; Aminafshar, Mehdi
Abstract UF‐Feta cheese was analyzed among three plants for total microorganisms, aerobic spores and Bacillus cereus in three parts (core, rind and brine) during ripening and shelf life. Then, hemolysin BL, cereolysin A and cereolysin B genes as virulence factors were investigated in the B. cereus isolates. The results show that in spite of significant decrease of the total count, the variation of B. cereus spores and aerobic spores was not meaningful during shelf life. It may be due to the sporelation of B. cereus in severe condition of UF‐Feta cheese. The results also show that B. cereus is well adapted to Feta cheese condition with low pH, and can present up to the end of shelf life. Moreover, in the detection of toxin‐producing genes, 30% of isolates were found to carry three genes. In conclusion, B. cereus isolated from UF‐Feta cheese should be considered as potential enterotoxin producers. Therefore, new efforts should be undertaken to restrict these organisms during manufacturing for food safety. Practical Applications B acillus cereus is a foodborne pathogen found in dairy products. However, some studies were reported that this microorganism cannot survive at low pH like UF‐Feta cheese. The results of the present study indicate that B. cereus can tolerate the acidity and storage temperature. In addition, occurrences of toxin‐producing genes which include diarrheal toxins provide useful information in risk assessment of food poisoning caused by B. cereus. Thus, the presence of it in UF‐Feta cheese may be potential risk factors for consumer health and should be considered a serious public health hazard.